Analisis Penerimaan dan Kontribusi Pajak Restoran Terhadap Penerimaan Pajak Daerah pada BPPRD Kota Manado - Mintalangi, Syermi S.E.; Pinatik, Sherly; Suwetja, I Gede (Jurnal Sosial Teknologi, 2025)
Since the establishment of North Sulawesi with the center of government of Manado City as a regional autonomy area according to Law No. 38 of 2000, North Sulawesi, especially Manado City, must automatically be ready to finance its household needs. One of the sources that can be taken is regional taxes. Regional Taxes are the largest source of local revenue in Manado City, and one of the sources of regional tax revenue is restaurant taxes. Restaurant Tax is a tax levied on services provided by restaurants. A restaurant is a facility that provides food and/or beverages for a fee, which also includes restaurants, cafeterias, canteens, stalls, bars and the like, including catering services. The purpose of this study is to analyze the effectiveness of restaurant tax revenue and contribution to regional tax revenue in Manado City. The research method used is a descriptive analysis through the analysis of the effectiveness ratio and the level of contribution of restaurant taxes to regional tax revenues. The results of the study show that regional taxes in 2019 are very effective, in 2020 they are ineffective, in 2021-2022 they are less effective and in 2023 they are quite effective. The effectiveness of Manado City restaurant taxes in 2019, 2022 and 2023 is very effective, 2020 is ineffective and 2021 is less effective. Meanwhile, the contribution of restaurant taxes to Manado City regional taxes in 2019-2023 is still lacking.